SPECTRAL INVESTIGATIONS OF CM DRA - Kuznetsov, M. K.; Pavlenko, Y. V.; Pinfield, D.; Jones, H. (Одеські астрономічні публікації, 2010)
We present an analysis of a high resolution (R=47000) echelle spectra of the low-mass eclipsing binary CM Draconis, which were obtained on the 4.2-m William Herschel Telescope. Spectra were obtained for various phases of the orbit. There are some difficulties in echelle spectra processing of cool stars, since it is hard to get energy distribution in a large scale in such spectra. We proposed an efficient method for making the continuum of spectrum of cool stars. We refined the parameters (effective temperature, rotational velocity and metallicity) of the components of the system CM Dra using the method of stellar atmospheres. The data that we obtained are in good agreement with the results obtained by other authors. It is indicate on efficiency of our technique. The errors of temperature and metallicity determinations is about 100 K and 0.3 dex respectively.